The Opinions of Secondary School Mathematics Teachers about the Lesson Study - Elif Boran, Kamuran Tarım, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of this study is to search the opinions of the secondary school mathematics teachers about the lesson study. It is a qualitative study which aims to describe the opinions of teacher views and was carried out with six secondary school math teachers. The study group of the research is set by criterion sampling method and focus group discussion technique is used in data collection process. In the analyzing of the data, descriptive analyze is performed. It is found out that the teachers have the positive opinions (utilization of each other’s experiences, generating new ideas together, composing the ideal lesson plan that a student can learn best, bringing the teachers the skill of analyzing a subject multidimensional, and developing common affects) about the lesson study. Besides teachers expressed the opinion of the negative effects of Lesson Study such as the insufficient of time, being recorded by a camera, teaching in front of other teachers or in a different class, the difficulty of gathering together and making a common plan. In this regard as using camera and lecturing in other teachers’ and class’ environments excite teachers, it can be searched what can be done to prevent teachers from exciting in other lesson study researches.